2009
DOI: 10.4103/0377-4929.54993
|View full text |Cite
|
Sign up to set email alerts
|

Melasma: A clinicopathological study of 43 cases

Abstract: Melasma is a symmetrical hypermelanosis of the exposed skin characterized by brown macules on the sun-exposed areas of the skin. The present study was carried out on 43 patients to analyze the correlation between histopathological features with clinical and Wood's light examination. The study showed a clinical and histopathological discordance of 16.2%. Solar elastosis (55.8%) was the single most common histological finding apart from increased melanin concentration, epidermal flattening and dermal lymphomonon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…[19] Even histopathologically there may not be a correlation between the findings of the Wood's light examination and the histopathological depth of the pigmentation. [2021] The difference may be due to the non-attendance of patients with mild varieties of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Even histopathologically there may not be a correlation between the findings of the Wood's light examination and the histopathological depth of the pigmentation. [2021] The difference may be due to the non-attendance of patients with mild varieties of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wood's light examination may not be accurate in determining the depth of pigment. [2324] There is poor correlation between the classification based on Wood's light examination and histopathology [Figure 3]. …”
Section: Etiologymentioning
confidence: 99%
“…Malar pattern melasma is predominant in the southern region of India to a greater extent when compared with the northern region [6–8]. Achar et al demonstrated that an increased exposure to sun, pregnancy, use of oral contraceptives and use of cosmetics at least five times a week contribute to the exacerbation of melasma among the Indian population [7]. The effect of socioeconomic class of the patient, effect of previous treatments, menopause status and other concomitant conditions have not been evaluated in epidemiological studies conducted to evaluate the prevalence of melasma [911].…”
Section: Introductionmentioning
confidence: 99%